Derivation of Human Expressions in the Quran and Its Effect on the Existence of His Creator - Nuraini Nuraini; Sufira Rahmi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Every word in the Qur'an has its own meaning that cannot be replaced by other words, even though they appear synonymous. However, there are still many who interpret the meanings of insān, basyar, and nās with the same meaning, namely humans, wherever and whenever they are used. If we examine more deeply, it is found that the meaning and context of each of these words are different from one another, because if it is understood the meaning is the same between one and another, it will certainly lead to contradictions regarding the consistency of the Qur'an. Therefore, this study tries to look at the substance of the meaning of insān, nās, and basyar words. The approach used is a qualitative approach using the maudhū'i method. The data obtained will be analyzed by content analysis. From the research it was found that in general human expressions in the Qur'an consist of three forms, namely insān, nas and basyar. From the results of the analysis of the commentators related to the words insān, nas, and basyar have different meanings. Insān is a human expression to show human perfection in physical and spiritual aspects, as creatures equipped with reason, creatures who carry a mandate and will be responsible for all their actions, and insā is also used to express the negative nature of humans, as for one of the derivations of the word al- insan, namely al-ins which is often juxtaposed with the word al-jinn as a form of two things that are different in material and nature. The word nas is a human expression which is more numerous than insān as a communal meaning so that it gives birth to interaction between fellow humans as social beings. While the word basyar refers to the meaning of humans in physical appearance, as biological beings, it is often used in prophetic contexts, as a sign that the Prophets and Apostles are only ordinary humans like others physically.